Hormonal and Psychological Factors in The Management of Rheumatoid Arthritis in Women : Literature Review - Ningrum, Kadek Ardhyani Widya; Prawiragara, Fachrizal Arfani; Wardhani, Fitria Kusuma (Journal of Diverse Medical Research: Medicosphere, 2024)
Introduction. Rheumatoid arthritis (RA) is a chronic autoimmune disease that causes inflammation of the joints and can lead to systemic complications. The prevalence of RA ranges from 0.5% to 1% of the global population, with a higher incidence in women than men. This literature review aims to analyze current research related to hormonal and psychological factors that influence the management of RA in women. Methods. A search was conducted through databases such as PubMed, Scopus, Google Scholar, and ScienceDirect with the criteria of articles published within the last five years. Discussion. Results suggest that hormonal fluctuations, such as estrogen and progesterone, may affect RA symptoms, especially during pregnancy and menopause. In addition, psychological factors, including stress and depression, have a significant impact on quality of life and pain perception in RA patients. Thus, the management of RA requires a comprehensive approach that considers both hormonal and psychological factors. Conclusion. This review emphasizes the importance of patient education as well as recommendations for further research into the specific role of hormones in RA pathogenesis and the development of more integrated psychological interventions. Keywords. Rheumatoid arthritis, autoimmune disease, hormonal, psychological, quality of life